The level of domestic tourist satisfaction as they visit at Stadthuys Complex, Melaka based on their expectation and perceived value / Nor Hafizahtul Akmal Haji Omar (Faculty of Business Management, 2008)
This research is about a study of the domestic tourist satisfaction based on their expectation and perceived value. For indicate the level of tourist satisfaction, demographic factors, service quality and price will used to identify the level is. The demographic factors consist of hometown, age, gender, education level, level income, race, occupation and marital status. The service quality consists of product, personnel, service and image. Next, price will identify from entrance fee of the Stadthuys' Complex, Melaka. The survey is conducted in Jalan Kota, Melaka. The sample size for this study is 50 respondents. There were 50 questionnaires being distributed and 50 were return and complete. Data obtained using three methods that are secondary data, survey and observational and other data. Respondents are required to answer the questionnaires that contain element that needed for the research. Data are analyzed using Reliability Test, Pearson Correlation Analysis, Frequency Analysis, and Descriptive statistics through SPSS program. The result shows that whether tourist who visits to Stadthuys' Complex, Melaka is satisfy or dissatisfied.